2020
DOI: 10.1136/medhum-2019-011811
|View full text |Cite
|
Sign up to set email alerts
|

Eggs, sugar, grated bones: colour-based food preferences in autism, eating disorders, and beyond

Abstract: In 1913, eccentric French composer Erik Satie wrote a fragmentary, diary-like essay where he depicted a strikingly rigid diet consisting solely of white foods: eggs, sugar, coconuts, rice, cream cheese, fuchsia juice and so on. Satie’s brief essay has later been used as one of many puzzle pieces in attempts to retrospectively diagnose him with autism spectrum disorder. With Satie’s white meal as a starting point, this paper explores colour-based food preferences and selective eating in clinical and non-clinica… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 58 publications
0
9
0
Order By: Relevance
“…Among visual cues of food or beverage items, specific colors or shapes were found to be favorable to autistic participants, even though there was no consensus. Previous studies have found the visual appearance of foods to drive liking for autistic children (Sharp, Jaquess, & Lukens, 2013; Zampollo, Kniffin, Wansink, & Shimizu, 2012), and some autistic individuals tend to limit their food preferences based on the colors and shapes of food items (Hubbard, Anderson, Curtin, Must, & Bandini, 2014; Provost, Crowe, Osbourn, McClain, & Skipper, 2010; Strand, 2021).…”
Section: Resultsmentioning
confidence: 99%
“…Among visual cues of food or beverage items, specific colors or shapes were found to be favorable to autistic participants, even though there was no consensus. Previous studies have found the visual appearance of foods to drive liking for autistic children (Sharp, Jaquess, & Lukens, 2013; Zampollo, Kniffin, Wansink, & Shimizu, 2012), and some autistic individuals tend to limit their food preferences based on the colors and shapes of food items (Hubbard, Anderson, Curtin, Must, & Bandini, 2014; Provost, Crowe, Osbourn, McClain, & Skipper, 2010; Strand, 2021).…”
Section: Resultsmentioning
confidence: 99%
“…A further cause of the atrophy of CN II is the deficiency of vitamin B12, which may be preceded by a gradual decrease in visual acuity [ 39 ]. Vitamin deficiencies are a frequently observed phenomenon in children with ASD due to the adherence to selective diets resulting from behavioral disorders and sensory sensitivities, in which children eat only color-selected foods [ 40 ]. In contrast to the aforementioned ideas, there are contrary articles in literature that do not indicate any deviation from normal fundus detail [ 18 , 34 , 41 , 42 , 43 ].…”
Section: Ophthalmic Manifestationsmentioning
confidence: 99%
“…Of course, as well as any literal crossmodal associations between colors and flavors (presumably based on associative learning) which may guide our flavor expectations, it is also worth noting that the visual appearance of food can take on a more symbolic meaning. This is perhaps especially clear in the case of the achromatic colors white and black, linked to purity/cleanliness and mourning, respectively (e.g., see Huysmans, 1884Huysmans, /1926Weineck, 2006;Carter, 2011;Harris, 2011;Spence and Piqueras-Fiszman, 2014;Piepenbring, 2016;Spence, 2018dSpence, , 2020aStrand, 2020). Furthermore, there is also a growing literature on the existence of more abstract crossmodal correspondences between color patches, or combinations of colors, and basic tastes and aromas (e.g., see Wan et al, 2014b;Spence et al, 2015;Spence, 2020b).…”
Section: Blue Food: Desirable or Disgusting?mentioning
confidence: 99%